Neonatal healthcare professionals' experiences of intact cord resuscitation in the mother´s bed- an interview study - Katarina Patriksson; Ola Andersson; Li Thies-Lagergren; Maria Rönnerhag (BMC, 2024)
Abstract Background Intact cord resuscitation in the first three minutes of life improves oxygenation and Apgar scores. The practise of intact cord resuscitation implies the umbilical cord still being connected to the placenta for at least one minute while providing temperature control and equipment for resuscitation. Healthcare professionals described practical challenges in providing intact cord resuscitation. This study aimed to explore neonatal healthcare professionals' experiences of providing intact cord resuscitation in the mother's bed. Method An interview study with an inductive, interpretative approach was chosen and analysed according to reflexive thematic analysis by Braun & Clarke. An open interview guide was used and 20 individual interviews with neonatal healthcare professionals were performed. The study was conducted at five level I-III neonatal care units. In Sweden, resuscitation is performed either in or outside the labour room. Results The results contributed insight into the participants' experiences of prerequisites for providing neonatal care in intact cord resuscitation. The sense of the mother's vulnerability was noticeable, as the participants reported reducing the risk of exposure to protect and preserve the mother's integrity. The practical challenges in the environment involved working in a limited space. The desire for multi-professional team training comprised education and training as well as debriefing to manage intact cord resuscitation. Conclusion The result of the present study highlights the fact that neonatal healthcare professionals' experiences of providing ICR in the mother's bed were positive and had significant benefits for the neonate, namely zero separation between the neonate and parents and better physical recovery for the neonate. However, the fact that ICR in the mother's bed can be challenging in several ways, such as emotionally, managing environmental circumstances and ensuring effective team collaboration. Therefore, it is of the utmost importance that healthcare professionals are given the opportunity to reflect and train together as a team. Future recommendations are to summarize evidence-based knowledge to design guidelines for ICR situation.